Online evaluation method of coal mine comprehensive level based on FCE. - Ling Shen; Guoxun Jing; Qiang Zeng (PLoS ONE, 2021)
An online evaluation method of coal mine comprehensive level based on Fuzzy Comprehensive Evaluation method (FCE) is proposed. Firstly, following the principles of fairness, systematicness and hierarchy, taking research and development, production, sales, finance, safety and management as the first level indicators, a set of multi-level evaluation indicator system of coal mine comprehensive level combining objective and subjective evaluation indicators is established. Secondly, according to the characteristics of the indicator system, the specific process of FCE of coal mine comprehensive level is given. Then, taking SQL Server as the database management system and C#.NET as the development language, a set of B/S structure online evaluation system of coal mine comprehensive level based on FCE is designed and developed. Finally, the proposed method is applied to Coal group PM for test. The application shows that the method proposed can provide an efficient and convenient online evaluation platform to evaluate the comprehensive level of coal mines for the Coal group, and the horizontal and longitudinal comparison of the evaluation results can urge the coal mines to maintain their advantages and avoid their disadvantages, which is of some significance for improving the overall competitiveness of the Coal group.